Design of a 1x4 Optical Power Divider Based on Y-Branch Using III-Nitride Semiconductor - Nauval Franata; Retno Wigajatri Purnamaningsih (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
Optical communications are identified as a technology that is able to meet future demands. As a passive component of optical communication, optical power dividers play an essential role. We propose a novel 1x4 optical power divider design, which is a combination of an optical power divider design using a Y-branch and an optical power divider using rectangular waveguides utilizing mode coupling phenomena from our previous researched designs. The 1x4 optical power divider design using three Y-branches and utilizing mode coupling phenomena is described in this work. The design consists of three sections: an input Y-branch, rectangular waveguides, and two output Y-branches. By utilizing mode coupling phenomena with 3 rectangular waveguides, the optical power was transferred from one waveguide to its adjacent, so we obtained a wider splitting angle at the input Y-branch. The design was optimized using the beam propagation method (BPM) at a wavelength for optical communication of Î» = 1.55 Âµm. We optimized various parameters such as the width and thickness of the waveguide, splitting angles, coupling gaps, and coupling lengths by doing numerous experiments. The result shows that the proposed design was successfully split into four outputs with 0.14 dB power imbalance at four output ports and 0.12 dB excess loss through the design. The excess loss and power imbalance at varied wavelengths were also observed. The distribution of excess loss and power imbalance is almost stable through the C-band range (1530-1565 nm). The proposed design shows the possibility of a new wide-angle optical power divider design and demonstrates the development possibilities of optical interconnections at wavelengths of 1530-1565 nm.